2019
DOI: 10.1007/s00423-019-01827-5
|View full text |Cite
|
Sign up to set email alerts
|

Volume-outcome correlation in adrenal surgery—an ESES consensus statement

Abstract: Background Published data in the last decade showed that a majority of adrenal operations are done by surgeons performing only one such case per year and based on the distribution of personal workloads 'high-volume' surgeons are defined as those doing 4 or more cases/year. Purpose This paper summarises literature data identified by a working group established by the European Society of Endocrine Surgeons (ESES). The findings were discussed during ESES-2019 conference and members agreed on a consensus statement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 78 publications
0
45
0
1
Order By: Relevance
“… 5 , 23 , 25 The shorter hospital stay may allow also reducing costs of hospitalization and a higher turnover of patients in surgical units, thus balancing the principal drawback of robotic platform of higher costs. 6 , 8 , 26 Brunaud et al calculated that robotic approach was 2.3 times more expensive than laparoscopic one, 6 but notably, costs could be curtailed by increasing the annual workload of robotic surgical procedures in high-volume centers, 4 , 26 leading also to a facilitation of the learning curve. From this cost-saving standpoint, the widespread adoption of robotic technology may conduct to a beneficial effect on robotic purchase, but published data at present are not sufficient yet and further studies are necessary.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 5 , 23 , 25 The shorter hospital stay may allow also reducing costs of hospitalization and a higher turnover of patients in surgical units, thus balancing the principal drawback of robotic platform of higher costs. 6 , 8 , 26 Brunaud et al calculated that robotic approach was 2.3 times more expensive than laparoscopic one, 6 but notably, costs could be curtailed by increasing the annual workload of robotic surgical procedures in high-volume centers, 4 , 26 leading also to a facilitation of the learning curve. From this cost-saving standpoint, the widespread adoption of robotic technology may conduct to a beneficial effect on robotic purchase, but published data at present are not sufficient yet and further studies are necessary.…”
Section: Discussionmentioning
confidence: 99%
“…From this cost-saving standpoint, the widespread adoption of robotic technology may conduct to a beneficial effect on robotic purchase, but published data at present are not sufficient yet and further studies are necessary. 26 , 27 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The small sample size limits statistical power and inferences as well as precluding meaningful subgroup analyses. Based on recent evidence for volume–outcome correlation in adrenal surgery, the European Society of Endocrine Surgeons 30 has recommended that the care of ACC should continue in centres performing at least 12 adrenal operations per year. As this is an observational study, there was some selection bias.…”
Section: Discussionmentioning
confidence: 99%
“…Two surveys conducted by the American Association of Endocrine Surgeons (AAES) reported that surgical residents performed 2 neck dissection procedures prior to their graduation, while clinical fellows in endocrine surgery performed 6–15 procedures during their 2-year fellowship program with 12 procedures being the cut-off number of procedures required to obtain competency [ 3 , 4 ]. Mihai et al recently analyzed the current practice in adrenal surgery worldwide [ 5 ]. The results reported were far from being encouraging.…”
Section: Discussionmentioning
confidence: 99%